Photobehaviour of Z-1, 2-di-(3′-methoxynaphth-2′-yl)ethene as model compound of biphotochromic supermolecules with Z-ethenic bridge. (2001) - Ortica, F.; Levi, D.; Brun, P.; Guglielmetti, R.; Favaro, G.; Mazzucato, U.
Abstract : This work is part of a research project aimed at investigating the behaviour of biphotochromic supermolecules where two photochromic units of the spirooxazine or chromene series are linked through a conjugated or unconjugated spacer. Preliminary investigations showed that the compounds with ethane, acetylene or ester bridges behave as classical photochromes while those with an ethene bridge showed good coloration accompanied by unusual thermal irreversibility at room temperature. The temperature effect on the spectral behaviour allowed such irreversibility to be explained by the occurrence of a cyclization process at the central ethene bond, typical ofZ -diarylethenes. To better understand this photobehaviour, a deep investigation of a model molecule, Z -1, 2-di-(3 ′ -methoxynaphth-2 ′ -yl)ethene, was carried out. This paper reports the results obtained on the model molecule and two biphotochromic systems containing benzochromene and spirooxazine units.